Chronological evidence of microplastic accumulation and contamination onset in Central Baltic Sea sediments - Chang, Cheng; Augustsson, Anna; Shahabi-Ghahfarokhi, Sina; Rahmati-Abkenar, Mahboubeh; Josefsson, Sarah; An, Lihui; Ketzer, Marcelo (Frontiers in Marine Science, 2025)
Microplastics (MPs) are a significant environmental concern due to their abundance, widespread occurrence, slow degradation rate, and toxicity. Although MPs have been found in various environments and organisms (including humans), few studies have investigated their historical accumulation in marine settings. Here we present the first chronological accumulation of MPs in Baltic Sea sediments over time. The high sediment accumulation rates (ca. 1 cm yr-1) and anoxic bottom conditions in the study area allowed for an exceptionally well-preserved record of MPs in sediment over the last 50 years. Despite potential biases and limitations associated with the methodologies (e.g., visual identification), our results suggest that MP accumulation began in the 1970s-1980s and has continued to increase until present-day, with up to 4450 particles per kg of dry sediment. The temporal distribution of MPs in sediment is consistent with local population growth in catchment areas and global plastic production rates, highlighting the impact of human activities on MP pollution in the region.